Strain rate and flame orientation statistics in the near-wall region for turbulent flame-wall interaction. Issue 5 (3rd September 2018) - Zhao, Peipei; Wang, Lipo; Chakraborty, Nilanjan
Abstract: Flame–wall interaction (FWI) in premixed turbulent combustion has been analysed based on a counter-flow like configuration at the statistically stationary state. For the present configuration, the two FWI sub-zones, i.e the influence zone and the quenching zone, can be identified from the DNS results. Detailed analysis of the important quantities, such as the flame temperature, flame–wall distance, wall heat flux, flame curvature and dilatation (including the flame normal and tangential strain rates), and some orientation relations between the flame normal and the principal strain rate directions, have been reported, together with the physical explanations. All these statistical results are determined by the relative strengths of the wall heat flux, thermal expansion and the flame–turbulence interaction.